Atlas of Coronary Intravascular Optical Coherence Tomography - Kini, Annapoorna (Springer International Publishing, 2018)
This atlas is a practical and fully illustrated guide to the use of intravascular OCT in diagnosis and treatment of coronary artery disease. It consists of two parts. The first part of the book provides a systematic introduction to coronary imaging with OCT. It describes how to interpret images and describes abnormal findings seen in atherosclerosis, complications after intervention, and stent assessment. The second part of the book presents real-life case studies that show how OCT is used in clinical practice in Mount Sinai to assess the disease, select appropriate treatment, and evaluate complications and results. Each case includes a brief clinical history, procedure summary, angiography and OCT images, including video material, and a discussion of how OCT affected the clinical decision-making process.